2000
DOI: 10.1111/j.1601-0825.2000.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium lauryl sulphate, triclosan and zinc on the permeability of normal oral mucosa

Abstract: OBJECTIVE: Sodium lauryl sulphate (SLS), an important component in many oral health products, is well established as a contact irritant in skin. Recent studies have suggested that it may also affect the structural integrity of oral mucosa. SLS is rarely used alone in dentifrices or mouthwashes and the aim of this study was to establish the effect of SLS both alone and in combination with Triclosan (TCN) and zinc (Zn) on the permeability barrier properties of normal human oral mucosa. METHOD: Ventral tongue muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…This observation is in concordance with the previously reported clinical effects of SLS on OM (10,11). Disruption of the epithelial surface layers of OM has also been described in previous in vitro studies on cadaver OM from humans (17) and pigs (20) after exposure to SLS. In the present study, a disruption of the epithelium with cell death in superficial cell layers was observed at lower clinical SLS concentrations (£0.15%) than previously reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in concordance with the previously reported clinical effects of SLS on OM (10,11). Disruption of the epithelial surface layers of OM has also been described in previous in vitro studies on cadaver OM from humans (17) and pigs (20) after exposure to SLS. In the present study, a disruption of the epithelium with cell death in superficial cell layers was observed at lower clinical SLS concentrations (£0.15%) than previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…The present study is, to our knowledge, the first to show that SLS has a dual biological effect on in vitro human OM at low versus high clinically relevant concentrations. This is partly in contrast to previous studies that have mainly addressed the destructive effects of SLS on OM (14,17). Careful consideration should be taken interpreting the in vitro experimental data in terms of potential clinical relevance.…”
Section: Discussionmentioning
confidence: 79%
“…Sodium lauryl sulfate (SLS) is a detergent that can change the barrier properties of human oral mucosa in vitro and in vivo , and increases gingival blood flow . Sodium lauryl sulfate‐containing toothpastes are associated with a more frequent occurrence of aphthous ulcers , and SLS‐free toothpastes can decrease the duration of ulcers and reduce pain .…”
mentioning
confidence: 99%
“…However, it is clear that the oral surfaces are substantially less permeable to water than the most permeable epithelial tissues, such as those of the thick descending limb of Henle or the alveolar surface, but are more permeable (by 10‐ to 100‐fold in direct comparisons) than epithelial tissues such as skin (Selvaratnam et al , 2001). Furthermore, on the basis of water permeability coefficients for the ventral tongue epithelium (Healy et al , 2000), the estimated surface area of human oral mucosa (Collins and Dawes, 1987), and the osmolarity differential between whole unstimulated saliva vs plasma (assuming that the osmolality of saliva is equivalent to 0.15% saline vs 0.9% for plasma), Dawes (2004) estimated that the maximum rate of fluid absorption from the oral mucosa to be 0.19 ml min −1 . While this value is only an estimation that relies on multiple uncertainties, it suggests that absorption is a significant mode by which fluid is lost from the oral cavity.…”
Section: Water Flux Across the Oral Mucosamentioning
confidence: 99%
“…For example, Lesch et al (1989) calculated the water permeability constants (K p ) for regions of the human oral mucosa which were derived from the buccal mucosa (K p = 8.22 · 10 )7 cm s )1 ), lateral border of the tongue (K p = 1.59 · 10 )7 cm s )1 ), and the floor of the mouth (K p = 1.74 · 10 )6 cm s )1 ). Additional studies examining water permeability across oral surfaces reported higher permeability coefficients of 8.0 · 10 )6 cm min )1 for ventral tongue and 6.67 · 10 )6 cm s )1 for primary cultures of buccal mucosa (Healy et al, 2000;Howie et al, 2001;Selvaratnam et al, 2001). Differences in experimental approaches limit the direct comparison of water permeability between the oral mucosa and other epithelial tissues.…”
Section: Water Flux Across the Oral Mucosamentioning
confidence: 99%